2020
DOI: 10.1590/1678-4162-11293
|View full text |Cite
|
Sign up to set email alerts
|

Does supplementation of vitamin C, reduced glutathione or their association in semen extender reduce oxidative stress in bovine frozen semen?

Abstract: The aim of this study was to evaluate the addition of vitamin C, reduced glutathione and the association thereof to the bovine semen cryopreservation extender. The ejaculate from nine bulls were divided into four fractions, each corresponding to a treatment, namely: control group-semen diluted with Tris-yolk extender; vitamin C group-semen diluted in Tris-yolk extender supplemented with vitamin C (2.5mmol/mL); glutathione group-semen diluted in Tris-yolk extender supplemented with reduced glutathione (2.5mmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…During cryopreservation, spermatozoa are exposed to various stress which eventually leads to decreasing of the fertilizing capability of sperm. Hence, several records have engrossed on improving sperm quality and reducing the negative impacts of OS by adding of antioxidants [ 17 ] and nanoparticles [ 7 , 11 , 13 , 18 ], but no reports were conducted to use the curcumin nanoparticles in cryopreserved rabbit semen. It is well accepted that if the particles have low zeta potential values, then there will be no force to avoid the particles pending flocculating and together.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During cryopreservation, spermatozoa are exposed to various stress which eventually leads to decreasing of the fertilizing capability of sperm. Hence, several records have engrossed on improving sperm quality and reducing the negative impacts of OS by adding of antioxidants [ 17 ] and nanoparticles [ 7 , 11 , 13 , 18 ], but no reports were conducted to use the curcumin nanoparticles in cryopreserved rabbit semen. It is well accepted that if the particles have low zeta potential values, then there will be no force to avoid the particles pending flocculating and together.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, several reports indicated that cryopreservation induced alteration in DNA integrity, lipid peroxidation, ROS, cholesterol content, capacitation [ 34 ], and acrosome reaction in spermatozoa and resulted in failure male fertility potential [ 5 , 7 , 17 ]. However, it has been reported that curcumin has a protective effect on DNA damage, normal development of testicular tissue and avoidance of spermatogenic cell apoptosis [ 12 , 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Zakošek et al (2021) had shown that enrichment of a sperm extender with calcium (Ca ++ ) to raise sperm quality posthawing and consequently improves fertility by decreasing cryopreservation-induced sperm damage. In addition, Pinto et al (2020) extender's supplementation with Vitamin C has shown positive impacts on sperm motility and preservation of plasma and acrosomal membranes throughout semen cryopreservation. Also, Espina-Ávila et al (2021) reported that Adding vitamins immediately to semen extenders enhanced the properties of the semen after thawing.…”
Section: Productive Performancementioning
confidence: 99%